Development of a database system for the collection of the Philippine General Hospital Department of Radiology - Enriquez, Lorebelle Q.; Paz, Maria Cristina T.; Carcellar, Marie Desiree R. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Facilitating access to a collection has been the guiding principle to the organizational systems created for the different collections and libraries. With the dynamic development in technology automation has aided the organization process done for librarians and information professionals.
The Department of Radiology of the Philippine General Hospital houses a collection of books, journals, videotapes and radiographs that have accumulated throughout the years. The bulk of the collection is concentrated on the radiographs that are used by the resident radiologists and medical students. The condition of the unorganized collection of the development has been a main concern of the staff and radiologists. The manual system of searching for a material used by the department does not effectively provide an easy access to the collection. The development of a database system for the collection of the department intends to solve the problems encountered by the users of the collection. This study primarily includes the organization and automation of the collection by achieving these main objectives: 1) to know how the collection of the department will be organized; 2.) to identify what features of a database are needed or desired by the users; and 3.) To determine if the database satisfied the needs of the users.
For the system development, the following phases suggested by Rowley were used: 1) definition of objectives; 2.) definition of system requirements; 3.) design; 4) implementation and 5.) evaluation. Analysis of the current system and the determination of the needs of the users were initially done by conducting interviews with the key personnel in the department. Through the initial needs analysis, the features desired by the users were determined. The following features were included in the database: 1.) easy to use; 2.) easy to learn; 3.) easy to perform searches; 4.) information on the status of the item; 5.) user friendly and 6) generation of reports by printing and saving. An evaluation of the database that has been created through the course of this study was also done by conducting a survey with the administration staff and the resident radiologists in the department. Results of the survey revealed positive remarks from the respondents.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine General Hospital. Department of Radiology; Database design -- Philippines -- Manila; Information organization -- Philippines -- Manila